Virtual reality simulation training in endoscopy: a Cochrane review and meta-analysis - Khan, Rishad; Plahouras, Joanne; Johnston, Bradley C.; Scaffidi, Michael A.; Grover, Samir C.; Walsh, Catharine M. (Endoscopy, 2019)
Background Endoscopy programs are increasingly integrating simulation training. We conducted a systematic review to determine whether virtual reality (VR) simulation training can supplement and/or replace conventional patient-based endoscopy training for health professional trainees with limited or no prior endoscopic experience.Methods We searched medical, educational, and computer literature databases in July 2017 for trials that compared VR simulation training with no training, conventional training, another form of simulation training, or an alternative method of VR training. We screened, abstracted data, and performed quantitative analysis and quality assessment through Cochrane methodology.Results We included 18 trials with 3817 endoscopic procedures. VR training provided no advantage over no training or conventional training based on the primary outcome of composite score of competency. VR training was advantageous over no training based on independent procedure completion (relative risk [RR] = 1.62, 95 % confidence interval [CI] 1.15 – 2.26, moderate-quality evidence), overall rating of performance (mean difference [MD] 0.45, 95 %CI 0.15 – 0.75, very low-quality evidence), and mucosal visualization (MD 0.60, 95 %CI 0.20 – 1.00, very low-quality evidence). Compared with conventional training, VR training resulted in fewer independent procedure completions (RR = 0.45, 95 %CI 0.27 – 0.74, low-quality evidence). We found no differences between VR training and no training or conventional training for other outcomes. Based on qualitative analysis, we found no significant differences between VR training and other forms of simulation training. VR curricula based in educational theory provided benefit with respect to composite score of competency, compared with unstructured curricula.Conclusions VR simulation training is advantageous over no training and can supplement conventional endoscopy training. There is insufficient evidence that simulation training provides benefit over conventional training.